South African adult caregivers as "protective shields": Serving as a buffer between stressful neighborhood conditions and youth risk behaviors. Issue 8 (23rd August 2019) - Small, Latoya A.; Parchment, Tyrone M.; Bahar, Ozge Sensoy; Osuji, Hadiza L.; Chomanczuk, Aminda Heckman; Bhana, Arvin
Abstract : Abstract: Low‐income youths in KwaZulu‐Natal, South Africa, face elevated risks to their well‐being from exposure to neighborhood conditions correlated with engaging in risky behaviors. These risks can be mitigated through adult caregivers who serve as protective shields, buffering adverse conditions. However, this protective role is dependent on the caregivers' mental health and well‐being. This secondary analysis uses baseline data from 475 child‐caregiver dyads in an HIV‐prevention program to examine the mediating effects of caregiver mental health on the relationship between neighborhood conditions and child risk‐behaviors. Multivariate analyses identify the direct and indirect effects of neighborhood stressors and caregiver mental health on child risk‐behavior. Findings suggest that caregivers mitigate the impact of neighborhood conditions on their children, but caregivers' mental health is directly affected by neighborhood conditions. Therefore, caregivers' mental health and well‐being must be considered key elements in developing youth risk‐behavior interventions.